PENGARUH GAYA BELAJAR VISULA, AUDITORY DAN KINESTHETIC TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA MTS NWDI PRINGGASELA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to determine whether there is a significant effect of visual, auditory, and kinesthetic learning styles on students’ mathematical reasoning ability in the topic of Systems of Linier Equations with Two Variables (SLETV). The research employed an ex post facto method involving 51 eighth-grade students of MTs NWDI Pringgasela in the 2025/2026 academic year. Data were collected through a learning style questionnaire, a mathematical reasoning ability test, and interview guidelines. The test instrument consisted of items measuring indicators of mathematical reasoning ability, while interviews were conducted with six students who obtained the highest learning style scores to strengthen the analysis results. The findings revealed that partially, visual, auditory, and kinesthetic learning styles have a positive and significant effect on students’ mathematical reasoning ability, with a significance value of This indicates that there is a positive relationship between students’ learning styles and their mathematical reasoning ability. The interview analysis further supports the findings, showing that visual learners tend to organize solution steps systematically and structurally, auditory learners understand better through verbal explanations and repetition, while kinesthetic learners comprehend more effectively through direct hands-on activities.This study demonstrates that learning style is a significant factor in supporting students’ mathematical reasoning ability. Therefore, it can be considered in designing more effective instructional strategies for the topic of Systems of Linier Equations in Two Variables (SLETV).